Players - los fotógrafos de Magnum entran al juego = Players - Magnum photographers come out to play - De Middel, Cristina 1975-; Parr, Martin 1952- (La Fábrica, 2018)
In order to go beyond the rules and the veneration that have characterised the development of photography since its beginnings, it is necessary to transgress, to invent, to play and to flirt with freedom. In this sense, there haven't historically been many authors who have dared to question the medium and turn it around, which confirms the impression that, as a language yet to be fully consolidated, photography hasn't been in the mood for jokes. But there are always authors, specially in the newer generations, who break the rules without vindications, just out of curiosity, seeking to have and portray fun. Exhibition: Espacio Fundación Telefónica, Madrid, Spain (09.05.-16.09.2018)
Ausstellungsdaten ermittelt: Catalog of an exhibition held at the Espacio Fundación Telefónica, Madrid, Spain, May 9-Sept. 16, 2018
Keywords: Magnum Photos Inc.; Freizeit -- Motiv; Fotografie; Spaß; Sport -- Motiv; Humor -- Motiv; Motiv; Photography, Artistic / Exhibitions; Ausstellungskatalog -- Espacio Fundación Telefónica -- 09.05.2018-16.09.2018 -- Madrid; Bildband